The Affective Neuroscience of Sexuality: Development of a LUST Scale - Fuchshuber, Jürgen; Jauk, Emanuel; Hiebler-Ragger, Michaela; Unterrainer, Human Friedrich (Frontiers in Human Neuroscience, 2022)
Background: In recent years, there have been many studies using the Affective Neuroscience Personality Scales (ANPS) to investigate individual differences in primary emotion traits. However, in contrast to other primary emotion traits proposed by Jaak Panksepp and colleagues, there is a considerable lack of research on the LUST (L) dimension - defined as an individual’s capacity to attain sexual desire and satisfaction - a circumstance mainly caused by its exclusion from the ANPS. Therefore, this study aims to take a first step towards the development of a standardized self-rate measurement for the L-disposition. For this purpose, two versions of the L-scales (L-12 and L-5) were developed and evaluated regarding reliability and aspects of validity. Materials and Methods: After a pilot study (N = 204; female: 81%) with an initial 20-item pool item reductions were conducted. This led to the construction of a 12-item (L-12) version and a 5-item version (L-5), which were assessed in a second sample consisting of 371 German-speaking healthy adults (58.50% female) aged 18 to 69 years (M=28; SD=9.75). Aspects of external validity were assessed by investigation of correlations with the ANPS, psychiatric symptoms (Brief Symptom Inventory-18), attachment security (Adult Attachment Scales) and personality functioning (Operationalized Psychodynamic Diagnostics Structure Questionnaire). To evaluate structural validity, both L-scales were investigated via confirmatory factor analysis (CFA). Results: Cronbach’s α indicated excellent internal consistency regarding L-12 (α=.90), while L-5 showed acceptable reliability (α=.82). CFA of a bifactor model of the L-12 indicated excellent model fit. Moreover, an excellent model fit was observed regarding a single factor model of L-5. For both scales moderate positive correlations were observed with SEEKING, PLAY and secure attachment, while they exhibited moderate negative correlations with SADNESS, insecure attachment, lower personality functioning, and increased psychiatric symptom load. Conclusion: Both newly developed scales exhibit satisfying psychometric properties, indicating high reliability, good structural validity and plausible correlations with external criteria. Hence, this study poses an important step towards the operationalization of the LUST concept. However, more research is needed in particular with respect to the scale’s external validity and its applicability in clinical populations.